Project Managers Are the Best Candidates to Manage Innovation - Lavalle, Arturo; Casale, Oliviero (International Journal of Advanced Corporate Learning (iJAC), 2020)
New technologies are changing our society bringing both great opportunities and enormous risks; therefore it is of paramount importance to understand how to cope with the ongoing digital transformation and how to manage the innovation it brings in all sectors and at all levels. The ability to innovate is a crucial factor for long-term corporate success. Everybody agrees on the importance to bring innovation within companies and organizations but there is little consensus on how to do it. Over the last years, a strong debate has raised on the identification of innovation manager’s tasks and duties and, above all, on the background and skills that this new professional profile should possess in order to effectively manage innovation. Very often, the innovation manager is seen as someone mostly resembling to a R&D or an IT Manager. Nevertheless, innovation is not only technology-led but encompasses a broader variety of aspects. This suggests that a different and more comprehensive background should be considered when codifying the innovation manager profile. This paper intends to identify this background by showing the strict correlation between project management and innovation management with the aim to emphasize why project management should represent the proper competency and experiential framework for innovation managers.